2014
DOI: 10.4236/ajibm.2014.46039
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Supply and Demand of Volunteers

Abstract: This work aims at describing the trends observed since the beginning of the crisis in the supply of and demand for volunteers. Few works exist that examine this dynamic, for the lack of recent data, and because the study of the demand for volunteers and for volunteers services is still rather undeveloped. Some hints appear that indicate: 1) an increase in the stock of volunteers, but not in every country, 2) an increase in demand for volunteers services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
1
0
4
Order By: Relevance
“…Institutions are here understood as cultural products that facilitate and support collective action, in which subjects are coordinated and act jointly. Studies demonstrated, theoretically and empirically, that many successful institutions are rich mixtures of "private-like" and "public-like" not necessarily based on legal regulation quite the contrary on community-based solutions [27] [28]. There is a strict correspondence between the mechanisms, the system of rules and the ESD of Messina's governance structures, with the eight "design principles" identified by the theory for a stable local common-pool resources management.…”
Section: The Modelmentioning
confidence: 99%
“…Institutions are here understood as cultural products that facilitate and support collective action, in which subjects are coordinated and act jointly. Studies demonstrated, theoretically and empirically, that many successful institutions are rich mixtures of "private-like" and "public-like" not necessarily based on legal regulation quite the contrary on community-based solutions [27] [28]. There is a strict correspondence between the mechanisms, the system of rules and the ESD of Messina's governance structures, with the eight "design principles" identified by the theory for a stable local common-pool resources management.…”
Section: The Modelmentioning
confidence: 99%
“…Quais os resultados percebidos? IPEA, 2006;CBVE, 2012;HAHN et al, 2014;INSTITUTO ETHOS, 2010;FLAMMER, 2013;VAN DER BYL, SLAWINSKI, 2015;DEITZ, MYERS, STAFFORD, 2012;PELOZA et al, 2012;HAYNES, JOSEFY, HITT, 2015;SCHENKELL, ERMANOL, MARIANO, 2014;VOEGTLIN, 2015;MADSON, WARD, ROYALTY, 2012;RODELL et al, 2016. Benefícios para a organização…”
Section: O Voluntáriounclassified
“…Além disso, apesar de o voluntariado empresarial nas organizações ser tema amplamente discutido no cenário internacional e brasileiro, poucas pesquisas mostram a contribuição efetiva que esse elemento tem trazido para as empresas e os funcionários envolvidos (BOENIGK; SCHUCHARDT, 2015;DÁVILA, 2012;JONES WILLNESS;MADEY, 2014;PELOZA et al, 2012;RAFFAELLI;GLYNN, 2014;RODELL, 2013;LYNCH, 2015; SHANTZ; SAKSIDA; ALFES, 2014; SCHENKELL; ERMANOL; MARIANO, 2014;WILLNESS;MADEY, 2014). Dessa forma, esta pesquisa também poderá oferecer subsídios a empresários, dirigentes de empresas e gestores que desejam desenvolver ações no campo social.…”
Section: Introductionunclassified
See 2 more Smart Citations